Il Diritto: così la Musica, così la Vita - Orciani, Luca (Cultura giuridica e diritto vivente, 2016)
[Law like Music and Life] Luca Orciani reviews the recent book Interpretare. Dialogo tra un musicista e un giurista by Mario Brunello and Gustavo Zagrebelsky (Bologna, il Mulino, 2016). Through a very close dialogue, Authors move across two worlds, two performative disciplines, two passions. With a critical sensitiveness, Orciani points out the important topics focused in the book (interpretation, creativity, virtuosity, perfection, but not only), asking some questions that are essential in Music as in Law.